AN EXPLORATION OF GRAFFITI ON UNIVERSITY’S WALLS: A CORPUS-BASED DISCOURSE ANALYSIS STUDY - Al-Khawaldeh, Nisreen Naji; Khawaldeh, Imad; Bani-Khair, Baker; Al-Khawaldeh, Amal (Universitas Pendidikan Indonesia, 2017)
Graffiti have received a great attention from scholars as they have been considered a vital cultural phenomenon for many years (Trahan, 2011; Divsalar Nemati, 2012; Zakareviciute, 2014; Farnia, 2014; El-Nashar Nayef; 2016). Although there are extensive contemporary researches on graffiti in many disciplines, such as linguistics, cultural studies, politics, art, and communication (Pietrosanti, 2010; Farnia, 2014; Oganda, 2015), there are few studies exploring graffiti on classrooms’ walls in higher education milieus (Farnia, 2014). To the best knowledge of the researchers, very few studies were done on the Jordanian context (e.g. Al-Haj Eid, 2008; Abu-Jaber, et al., 2012) and none was done on the Jordanian universities. Therefore, this study aims at analysing the content and communicative features of writings found on universities’ classrooms’ walls, corridors, and washrooms and their relation to the socio-cultural values of the society in order to explore how universities help students voice their attitudes and thoughts. The linguistic features that characterise these writings were also examined. Graffiti-writings, which were collected from the University of Jordan and the Hashemite University, were coded and analysed using the thematic content analysis technique (Braun Clarke, 2006) and Critical Discourse Analysis (Fairclough, 1995). The analysis of the data has shown that graffiti serve different communicative language functions related to personal, social, national, religious, political, and taboo matters. The most salient linguistic features of these graffiti are simplicity and variation. It can be concluded that graffiti are distinctive and silent ways of communication, particularly in students’ society. The study will be of great importance to linguists, sociologists, educators, administrators, teachers and parents. It is enrichment to the available literature on linguistic studies.